2007
DOI: 10.1051/orthodfr:2007004
|View full text |Cite
|
Sign up to set email alerts
|

Jumeaux et héritabilité des phénotypes dento-faciaux

Abstract: RÉSUMÉ -En orthopédie dento-faciale, où facteurs génétiques et environnementaux s'interpénètrent depuis les premières phases du développement, le clinicien cherche à déterminer dans quelle mesure sa thérapeutique pourra influencer le schéma de croissance des patients. L'étude des jumeaux monozygotes (MZ) et dizygotes (DZ), dans leurs ressemblances, mais également dans leurs différences, apporte des éléments de réponse. . . mais soulève également de nombreuses questions. Nous reprenons dans cet article des étud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The resulting embryos have identical genotypes and are prone to manifest the same phenotypic characteristics. However, epigenetic influences and environmental interactions can cause changes in the individuals' phenotypic pattern [11], [12]. In this context, the studies of twins may to help understanding the development of dentocraniofacial characteristics and determining the inheritance of malocclusions.…”
Section: Researchmentioning
confidence: 99%
“…The resulting embryos have identical genotypes and are prone to manifest the same phenotypic characteristics. However, epigenetic influences and environmental interactions can cause changes in the individuals' phenotypic pattern [11], [12]. In this context, the studies of twins may to help understanding the development of dentocraniofacial characteristics and determining the inheritance of malocclusions.…”
Section: Researchmentioning
confidence: 99%
“…Studies on monozygotic twins may elucidate the genetics underlying the specific aspects of malocclusions and tooth anomalies in the analysis, improving the possibilities of performing a correct treatment plane [ 2 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fertilization of two oocytes creates dizygotic twins, and from the very beginning they develop as two different embryos, which have a similar genotype, so they are phenotypically similar to other siblings, which are not twins. Variations in dizygotic twins are mostly due to differences in genetic bases (5). Observing occlusal characteristics within families, Harris and Smith have concluded that most of the examined variables are under the influence of environmental factors, which is the consequence of the same living conditions within the family (6).…”
Section: Introductionmentioning
confidence: 99%